Sadar Penuh dengan Ber-Mindful Parenting dalam Kehidupan Sehari-Hari - Wistina Seneru; Ayu Andriyaningsih; Karsinah (LPPM STIAB JINARAKKHITA LAMPUNG, 2023)
The mindfulness parenting program is a form of informal activity carried out to align child care and education activities in playgroups and at home. There are several problems with the pattern of parenting children. This service aims to introduce the mindfulness parenting program to Buddhists in East Oku by providing education to parents so they have knowledge and insight on how to apply good and right parenting styles to children. The service is carried out in the form of workshop activities. As a result, Buddhists in East Oku, especially foster parents, have new insights on how to educate children in a fully mindful way.